Assessment of Dairy Production System, Handling, Processing and Utilization Practices in South Ari and Malle District of South Omo Zone, Ethiopia - Getaneh, Demerew (Research on World Agricultural Economy, 2023)
Milk is produced, processed and utilized in different parts of Ethiopia and the majority in rural areas is processed at the household level into milk products using traditional technologies and marketed through informal channels. This study was initiated to assess and describe the traditional knowledge of milk production, handling, processing and utilization practices in South Ari and Malle district. Three dairy potential Kebeles from each district were selected via a purposive sampling procedure. Then, 196 households were selected through a systematic random sampling procedure. Data were collected using a semi-structure questionnaire and analyzed by SPSS (Version 23) software. There was a significant difference (P < 0.05) in livestock composition across the study districts. About 75% in South Ari and 72.9% in Malle have their own grazing land. Feed shortage (73%) and improved breed access (26%) in South Ari, and feed shortage (52.1%), drought (44.8%) in Malle were among the main constraints affecting dairying. About 65% of South Ari used plastic buckets for milking and clay pots for fermentation and churning. In Malle 88.5% used calabash containers for milking, accumulation and churning. The average days of raw milk fermentation before churning in South Ari and Malle were 4.2±0.1 and 2.9±0.0 days. The average butter-making time was 63.4±1.8 minutes in both districts. The amount of milk fermented and butter produced from this fermented milk is significantly different (P < 0.05) across districts. Nearly 95% of South Ari milk is traditionally processed into yogurt, butter, buttermilk and cheese; and used for home consumption and marketing. However, in Malle 72.9% of yogurt and buttermilk processing is used for home consumption; and 26% of butter processing is only used for marketing. It is possibly concluded that dairy production was commonly practiced and it was a good source of income in both districts. Therefore, it is vigorous to support the dairy linkage with extension services by enhancing the input provision. ER